The Impact of Zakat Management in Banten Province on Improving the Quality of the Mustahiq Family - Riswandi, Dendi; Syafei, Rahmat; Athoillah, Mohammad Anton; Wulan, Elis Ratna (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2024)
Indonesia is still having difficulty overcoming the classic problems of wide disparities in wealth and high levels of extreme poverty. One solution that is an instrument for dealing with the phenomenon of extreme poverty and wealth disparities is zakat management. This study analyzes Zakat management's influence on fiscal, economic growth, and poverty on human development in Banten Province. This research uses a quantitative approach with a descriptive analysis method. The location of this research is in Banten Province. The data of sekunder with secondary data interval 2010-2019, and descriptive analysis method. The data collection using observation and documentation techniques. At the same time, the data analysis is through the classical assumption test, normality test and hypothesis testing. This study's results indicate that Zakat has a higher and positive and significant correlation between the variables of zakat on the human development index (HDI), meaning that the higher the role of zakat, the higher the Human Development Index (HDI). The enormous potential of zakat, if managed with correct, healthy, and accountable management, will be able to lift Mustahiq from the brink of poverty and become economically and fiscally empowered in the domestic family so that it can increase the human development index significantly. Therefore, related parties, namely the local government, BAZNAS, and the muzakki, are recommended to synergize to develop human development policy programs in Banten province.